Premedication Use in Preventing Acute Infliximab Infusion Reactions in Patients with Inflammatory Bowel Disease: A Single Center Cohort Study. Issue 10 (October 2017) - Gold, Stephanie L.; Cohen-Mekelburg, Shirley; Schneider, Yecheskel; Shen, Nicole; Faggen, Alec; Rupert, Amanda; Scherl, Ellen J.; Bosworth, Brian; Steinlauf, Adam
Abstract : Background: Infliximab (IFX) is commonly used in patients with inflammatory bowel disease. One common side effect of IFX is an acute infusion reaction. Despite the lack of evidence supporting their use, clinicians use various premedications to prevent acute reactions. We evaluated the effectiveness of premedications in the prevention of acute IFX infusion reactions. Methods: A retrospective cohort study was performed identifying patients with a diagnosis of inflammatory bowel disease who received IFX at our institution. Information about each IFX infusion was recorded, including the dose, infusion rate, use of premedications, and any reactions. Infusions were stratified into low and high risk. In the high- and low-risk groups, the relative risk was calculated for each premedication combination used in our institution. Results: Seven hundred seventy-three patients were identified; 578 patients (7090 infusions) met inclusion criteria and were included for analysis. Nine hundred eighty-six high-risk infusions were isolated; 620 (62.8%) of these infusions were administered with premedications (diphenhydramine and/or hydrocortisone) and 53 (5.4%) reactions occurred. Six thousand one hundred four low-risk infusions were identified; 2253 (36.9%) of these infusions had premedications and 61 (1.0%) reactions occurred. In both groups, none of the premedications used resulted in a significantly lower reaction rate compared with no premedication use. Conclusions: In both the high- and low-risk cohorts in this study, premedication use was not effective in reducing the rate of acute IFX reactions. Given this, routine premedication use is not recommended without future randomized control trials to demonstrate efficacy. Abstract : Article first published online 22 August 2017.